Theoretical demonstration of elastic wave guiding in a Pillar-Based phononic crystal slab - Mohd Syafiq, Faiz (Universiti Malaysia Perlis (UniMAP), 2021)
Link to publisher's homepage at http://ijneam.unimap.edu.my